All Welcome Here? Attitudes towards Muslim Migrants in Europe. (25th December 2020) - Gusciute, Egle; Mühlau, Peter; Layte, Richard
Abstract: Islam is becoming an increasingly prevalent religion in Europe due to large inflows of Muslims over the last few decades. Previous social survey research suggests that the European public is critical of immigration from Muslim countries with concerns relating to integration and security. Using the 7th round of the European Social Survey and linking it to other data sources, this paper examines whether threat hypotheses can explain anti‐Muslim sentiment in Europe. The study finds that opposition to Muslims is significantly higher than opposition to migrants in general, particularly in Eastern and Central Europe. The threat hypothesis is not supported on a country level as counties with higher "stock" of Muslim population and higher number of Islamic terrorist attacks are more welcoming towards further Muslim immigration. Furthermore, the study finds that women are more opposed to Muslim immigration than men. The wider implications of these findings and alternative explanations are discussed.